Changes in subfoveal choroidal thickness after uncomplicated cataract surgery - Gudauskiene, Gaile; Matuleviciute, Indre; Mockute, Ruta; Maciulaityte, Evelina; Zaliuniene, Dalia (Biomedical papers, 2019)
Background: Recent investigations show that phacoemulsification causing an inflammatory insult to the eye has an effect not only on retina but on the choroid as well. The purpose of this study was to evaluate the subfoveal choroidal thickness (SFCT) after uneventful phacoemulsification using swept-source optical coherence tomography (SS-OCT). Methods: This prospective study included 30 eyes of 23 patients with senile cataract undergoing uncomplicated phacoemulsification and intraocular lens implantation. SFCT and foveal retinal thickness (FRT) measurements were made at the same time, 1-2 PM preoperatively (P), 1 month (M1) and 3 months (M3) postoperatively using 1050 nm DRI Triton SS-OCT (Topcon, Tokyo, Japan). Postoperative changes in the SFCT, FRT and correlation of SFCT change with axial length, age, baseline intraocular pressure (IOP), IOP change were assessed. Results: The mean SFCT increased statistically significantly 3 months after surgery in all sectors except the superior inner region. Of the factors affecting the SFCT, the change in the SFCT (M3/P), correlation with age and baseline IOP in almost all sectors was observed. The mean FRT increased significantly after the surgery in all sectors. Conclusions: Insignificant subclinical increase in SFCT was observed 1 month after the cataract surgery. Significant increment in SFCT was detected 3 months postoperatively, which was correlated with surgery-induced IOP and ocular perfusion pressure change in the short term.
Keywords: choroid; phacoemulsification; optical coherence tomography